FAKTOR-FAKTOR YANG MEMPENGARUHI ALOKASI KREDIT PERBANKAN DI PROVINSI SUMATERA UTARA - Sihombing, Binsar (UNIKA Santo Thomas, 2010)
, His research is conducted to identify and analyze the determinant factors of bank loan in North Sumatera Province. To identify and analyze the determinant factors in bank loan is using the panel model. This model is using to estimate the elasticity of loan interest rate, deposit interest rate, intensity of competition or the numbers of bank office, the nominal Regional Gross Domestic Product [RGDP] and the Regional Gross Domestic Product [RGDP] by sectors towards bank loan. The panel model is choosing the fixed effect model [FEM] with RGDP as cross section specific coefficients. This model using the secondary data that published by BPS and Bank Indonesia Medan